Pengaruh Penggunaan Media Pembelajaran Berbasis Aplikasi (Kahoot) terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Fiqih Kelas VII di MTs Muhammadiyah 06 Banyutengah - Wahidah, Nisa’atul; Chotibuddin, M. (Jurnal Mahasiswa Pendidikan, 2021)
This research is motivated by the increasing development of technology in the era of the industrial revolution 4.0, educators can make learning innovations to make the learning process more interesting, namely by utilizing various programs that are able to produce an interactive learning media. The lack of use of learning media that is used especially in Fiqh learning, makes students' learning motivation decreases and feels bored in the learning process which tends to use conventional methods. One of the latest application programs that can be used as interactive learning media is the Kahoot educational game application. The purpose of this study was to determine whether there is an influence of application-based learning media (Kahoot) on student learning outcomes at MTs Muhammadiyah 06 Banyutengah. This study uses a quantitative approach with a One-group pretest-posttest research design and the number of respondents is 26 respondents, using sample data. Collecting data using pre-test and post-test questions. The collected data were analyzed by validity test, reliability test, normality test, homogeneity test, correlation test, significance test and coefficient of determination. Based on the calculation results obtained manually by testing the hypothesis using the product moment correlation formula, the results obtained are rcount = 0.730 > rtable = 0.3882. Meanwhile, for the significance test, the results obtained tcount = 5,228 > ttable = 2,063 at a significance level of 5%. From the discussion as mentioned above, it can be concluded that Ho is rejected and Ha is accepted or there is a positive and significant influence between Application-Based Learning Media (Kahoot) on Student Learning Outcomes in Fiqh Subjects Class VII at MTs Muhammadiyah 06 Banyu Middle School Year 2020/2021.